A little nightclub medicine: the healthcare implications of clubbing. Issue 6 (1st November 2002) - Luke, L C; Dewar, C; Bailey, M; McGreevy, D; Morris, H; Burdett-Smith, P
Abstract : Objective: To describe the scale and range of acute medical problems among patients who present to an inner city accident and emergency (A&E) department after attending nightclubs in Liverpool. Methods: From April 1997 to April 1998, all patients identified as having attended a nightclub before their arrival at the department were included in the study. Information regarding their attendance was gathered retrospectively using a standard proforma. Setting: A large, city centre, teaching hospital A&E department with an annual new patient attendance rate of over 95 000. Result: 777 such patients were enrolled in the study (0.81% of all new attendances during the same period). This was probably an underestimate, as some eligible patients were not identified during the study. Predictably, most presentations were at the weekend between midnight and 08.00. Suprisingly, the commonest mode of transport to the hospital was an ambulance (38%, 298 of the total). Assault accounted for most presentations (57%, 443 of the total) and lacerations were the commonest injury (the face being most frequently affected). Alcohol was the commonest intoxicant overtly associated with the A&E department attendance. Conclusions: Injury after assault is the commonest precipitant of hospital care among clubbers in Liverpool. Alcohol is the most important contributory factor, although illegal drug misuse is a considerable challenge in the clubs themselves. A number of measures such as (a) the introduction of unbreakable glass or plastic containers; (b) the elimination of glass from outside clubs; (c) the provision of high quality immediate medical care at larger venues; (d) the curbing of over crowding and cheap drinks promotions; (e) registration of doormen, and (f) targeted policing of the areas around nightclubs are urgently required to reduce the healthcare (and civic) burden of clubbing. The cost for these should be borne by the highly profitable clubbing and brewing industries. A national code of practice for clubs—already in existence voluntarily—should be made mandatory.